Z′-mediated dark matter freeze-in at stronger coupling - Giorgio Arcadi; David Cabo-Almeida; Oleg Lebedev (Physics Letters B)
We study freeze-in production of fermionic dark matter mediated by a Z′ gauge boson. In particular, we explore the regime of Boltzmann-suppressed production, when the Standard Model (SM) thermal bath temperature never exceeds the dark matter mass. The corresponding gauge coupling is then required to be significant, up to order one. As a result, this class of freeze-in models can be probed by the current and future direct dark matter detection experiments.